385 Who are you calling old? practice patterns and management of nonagenarians presenting to a gynecologic oncologist for initial consultation. (18th September 2019) - Ryan, E; Margolis, B; Pothuri, B
Abstract : Objectives: To describe the practice patterns and treatment of nonagenarians who initiated care with a gynecologic oncologist. Methods: Retrospective chart review of women aged 90 or older who presented to a gynecologic oncologist between 10/09 and 12/18 at an urban academic medical center. Descriptive statistics utilized for variables of interest. Results: We identified 34 nonagenarians (median age 92, range 90–98): 10 (29%) had benign disease, 8 (24%) pre-malignancy or suspected malignancy, and 16 (47%) malignancy. Of these, 79% had age and/or functional status discussed in the care plan. Of the 8 with suspected malignancy, 5 declined further workup. The cancer distribution revealed 5 (31%) vulvar, 5 (31%) uterine, 4 (25%) ovarian, 1 (6%) vaginal and 1 (6%) cervical cancers. Combined, 37% had stage I disease; 6% stage 3; 6% stage 4; 13% recurrent; and 25% unstaged. All received treatment plans: 7 (47%) with palliative intent and 8 (53%) with curative intent. In the curative group, 7 underwent surgery (1 adjuvant chemotherapy) and 1 chemotherapy/radiation. In the palliative group, 4 underwent radiation, 1 chemotherapy and 2 declined/unknown. Overall, 13 (87%) completed the proposed treatment. Treatment-related complications included 1 superficial skin infection and 1 thirty-day readmission. Conclusions: Nonagenarians often presented with vulvar or endometrial cancer and 87% successfully completed treatment with minimal adverse effects or toxicity. Age and/or functional status were considered in the care plan for 79% of women, but it did not preclude treatments that had the potential to preserve meaningful quality of life and/or cure patients of their disease.